ANALYSIS OF URBAN EXPANSION CHARACTERISTICS OF YANGTZE RIVER DELTA URBAN AGGLOMERATION BASED ON DMSP/OLS NIGHTTIME LIGHT DATA - M. Li; M. Li; W. Zhang; X. Zheng; K. Xu (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2022)
Urban agglomeration is the strongest driving force of national economic development. The formation and development of urban agglomeration is an important feature of modern urbanization process, and it is of great significance to study its spatial expansion and development process for regional sustainable development. Based on the DMSP/OLS nighttime light remote sensing data from 2000 to 2010, this paper uses threshold method to extract the urban built-up area of the Yangtze River Delta urban agglomeration. The expansion characteristics of urban built-up area in Yangtze River Delta urban agglomeration are analysed from three aspects: expansion area, expansion intensity and expansion type. The results show that the urban agglomeration in The Yangtze River Delta is experienced a rapid urban built-up area expansion process during the decade. The proportion of urban built-up area increased from 9.95% to 15.46%, the average nighttime light intensity increased from 10.18 to 23.43, and the type of urban built-up area expansion was filling type.